The impacts of land use change on ecosystem services in Rwanda: a case of Bugesera District - DUSENGIMANA, Jean Bosco; KAMUHANDA, Dr. James Kant; NSABIMANA, Bernard (International Journal of Scientific Research and Management (IJSRM), 2025)
The study titled "The Impacts of Land Use Change on Ecosystem Services in Rwanda: A Case of Bugesera District" investigates how agricultural expansion and urbanisation affect ecosystem services such as water quality, biodiversity, soil fertility, and carbon sequestration in Bugesera District. The research addresses concerns over environmental degradation driven by rapid land-use changes, which challenge sustainable development goals in the region. Using a mixed-methods approach, the study analyses satellite imagery and land cover maps from 2004 to 2024, alongside survey data from 99 local government employees. Statistical tools, including linear regression via SPSS, were used to assess the impact of land use changes on ecosystem services. The analysis revealed major shifts: agricultural land decreased by 51%, while built-up areas surged by 5,800%, indicating rapid urban growth fueled by population increase and infrastructure expansion. The findings showed a significant negative correlation between agricultural expansion and ecosystem services, with a decline of 0.061 in services per unit of agricultural growth. Urbanization had a mildly positive, though statistically insignificant, effect (coefficient of 0.077). Population and settlement growth, however, had a statistically significant positive effect (p = 0.038